Electrochemical characterization of Fe‐26Mn‐3A1‐7Cr alloy bipolar plate for PEMFC. (2nd October 2012) - Tian, Rujin
SUMMARY Corrosion behaviors of Fe‐26Mn‐3A1‐7Cr alloy are investigated in the solution of 0.05 M H2SO4 + 2 ppm F‐, and interfacial contact resistances (ICRs) are measured before and after potentiostatic polarization at operation potentials. The results show that passive current densities of Fe‐26Mn‐3A1‐7Cr alloy are about 10‐5 A cm‐2. Stable passive film forms on the surface of Fe‐26Mn‐3A1‐7Cr alloy in the cathodic side, and no pit is observed, while serious dissolution occurs in the anodic one. The ICR of Fe‐26Mn‐3A1‐7Cr alloy in anode side is about three times higher than that in cathode one. Copyright © 2012 John Wiley & Sons, Ltd.